Underemployment in a government institution: Conceptualization and its relationship with work variables - Ustare, Diane Marie A. (Animo Repository, 2007)
This thesis paper focused on underemployment in a government institution, its conceptualization and its relationship with work variables (i.e., job satisfaction and work outcomes). Using a mixed method approach for research design, the researcher conducted content analysis for qualitative method while descriptive statistics and correlation was applied for quantitative method. To form the sample, stratified random sampling was done to proportionally administer questionnaires to the employees from each sector of the government institution. Underemployment was measured using both objective and subjective underemployment criteria. Out of the 327 potential participants, 141 qualified as underemployed, however, only 129 were the actual participants who were further evaluated for Job Satisfaction Survey (JSS) and work outcomes (i.e. job performance and withdrawal behaviors) based on their performance evaluation form (PEF). Moreover, 21 participants who obtained the highest and lowest subjective underemployment scores were subjected to the FGD where the concept of underemployment was examined. FGD results revealed that selected government employees generally view underemployment as the underutilization of their education, experience, and skills. Statistic results show that subjective underemployment is decreases job satisfaction and fringe benefit is the only facet of job satisfaction that increases job performance. The implications of the results were discussed in the study.